The Effect of Celebrity Endorsement in TV Ads on Consumer Buying Decision of Fast-Moving Consumer Goods: A Perspective from the Theory of Planned Behavior - Mohammad Toufiqur Rahman; Hanim Hj Misbah; Syadiyah Abdul Shukor (Universiti Sains Islam Malaysia, 2024)
Page : 73-90